Cross-Cultural Education Strategies in Cultivating Multicultural Awareness from the Perspective of Legal and Citizenship Education - Wahyu Lailatul Baridah; Muhammad Erikko Abimayu; St.Wijdanah Ram (CV. Ulil Albab Corp, 2025)
This study aims to analyze cross-cultural education strategies in fostering multicultural awareness among junior high school students from the perspective of Legal and Citizenship Education. This study uses a qualitative library research approach, reviewing various scientific literature, accredited journals, and relevant educational policy documents. Data were collected through documentation techniques and analyzed using the Miles & Huberman model of thematic analysis. The results of the study indicate three main themes: (1) the integration of multicultural values ​​in PPKn learning, (2) cross-cultural dialogue as a means of internalizing values, and (3) inclusive school culture and multicultural leadership as a foundation for strengthening national character. These findings confirm that cross-cultural education contributes to the formation of legal and social awareness among students, while expanding the function of PPKn as an instrument of democratic character education. This study recommends the integration of cross-cultural strategies in the national education curriculum and policy.